2018
DOI: 10.1186/s12891-018-1935-8
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a predictor of hospital length of stay after elective total joint replacements in elderly patients

Abstract: BackgroundTotal joint replacement procedures are increasing in number because of population aging and osteoarthritis development. Defined as a lack of physiological reserves and the inability to adequately respond to external stressors, frailty may be more common than expected in older patients with degenerative arthritis awaiting total joint replacements.The aim of the present study was to assess associations between frailty and adverse outcomes, frailty prevalence among elderly patients awaiting elective TJR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
3
59
0
1
Order By: Relevance
“…17 Our study used the Clinical Frailty score as the frailty assessment tool. The Clinical Frailty score is well validated, [18][19][20][21][22] with Clinical Frailty score, the Frailty Index and the Frailty Phenotype the most commonly used frailty tools. 23 A systematic review looking at screening of frail patients in the ED found only four studies meeting the inclusion criteria and concluded that more randomised clinical trials of frailty screening tools compared to usual care are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our study used the Clinical Frailty score as the frailty assessment tool. The Clinical Frailty score is well validated, [18][19][20][21][22] with Clinical Frailty score, the Frailty Index and the Frailty Phenotype the most commonly used frailty tools. 23 A systematic review looking at screening of frail patients in the ED found only four studies meeting the inclusion criteria and concluded that more randomised clinical trials of frailty screening tools compared to usual care are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…12,38 One study using 2 different frailty assessment tools in elective total joint replacement patients showed that the frailty status categorized by the CFS was significantly associated with LOS while those categorized by FRAIL scale was not. 42 The CFS is based on the deficit accumulation model, 18 and the FRAIL scale is based more on Fried's phenotypic model. 20,42 The authors postulated that their study population, which consisted of elective orthopedic surgery patients, may have excluded more frail patients (eg, the hip fracture population).…”
Section: Postoperative Outcomes Associated With Frailtymentioning
confidence: 99%
“…In addition, LOS might have been increased because of other factors, such as the type of surgery and/or postoperative adverse events or intraoperative incidence. Hip, knee and spine surgery are complicated surgeries that often result in adverse events or postoperative complications, and extended LOS in frail patients is well documented Wang et al, 2018). 18Complications/adverse events, n (%) 53 265Postoperative delirium (POD), n (%) 25 12524 hour-postoperative 13 52Discharge day 12 48Discharge disposition, n (%) of inability to discharge home 22 (11%)…”
Section: Characteristics N (%) Mean (Sd) Rangementioning
confidence: 99%